2016
DOI: 10.1177/0886260516672940
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Bias Crime Injuries: A Comparative Analysis of Physical and Psychological Victimization Effects

Abstract: The core justification of bias crime statutes concerns whether bias-motivated crimes are qualitatively different from otherwise motivated crimes. We test the hypothesis that bias crimes are more detrimental than non-bias crimes by testing for multi-dimensional injuries to victims of bias and non-bias-motivated criminal conduct. Using National Crime Victimization Survey (NCVS) Extract 2013 Collection Year Incident-level Extract File, we analyzed physical injuries and psychological trauma to NCVS victims during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…These injuries are often related to the presence of weapons (Harlow, 2005;Strom, 2001), although reports of weapons use and rates of injuries have varied when examining different years and different data sources (Wilson, 2014). Bias crimes have been determined to be particularly heinous even in relatively "minor" crimes such as vandalism because of the increased levels of negative health and mental health outcomes for victims that are long-lasting, and that these crimes also have negative impacts to victims' communities that extend beyond non-bias crimes (Cogan, 2002;Fetzer & Pezzella, 2019). Scholars have noted that these differences are typically a matter of degree, rather than the presence or absence of a characteristic.…”
Section: Characteristics Of Bias Crimes and Bias Crime Perpetratorsmentioning
confidence: 99%
“…These injuries are often related to the presence of weapons (Harlow, 2005;Strom, 2001), although reports of weapons use and rates of injuries have varied when examining different years and different data sources (Wilson, 2014). Bias crimes have been determined to be particularly heinous even in relatively "minor" crimes such as vandalism because of the increased levels of negative health and mental health outcomes for victims that are long-lasting, and that these crimes also have negative impacts to victims' communities that extend beyond non-bias crimes (Cogan, 2002;Fetzer & Pezzella, 2019). Scholars have noted that these differences are typically a matter of degree, rather than the presence or absence of a characteristic.…”
Section: Characteristics Of Bias Crimes and Bias Crime Perpetratorsmentioning
confidence: 99%
“…Finally, hate-motivated violence may hurt more by exacerbating the physical consequences of victimization (Levin, 1999). Supporting this argument, a number of studies have demonstrated that, along with other serious consequences (e.g., psychological harms, harmful effects to the community), hate crime injuries are qualitatively more severe than other hate crimes (Fetzer & Pezzella, 2016; Iganski, 2001; Levin, 1999; Levin & McDevitt, 1993; Messner, McHugh, & Felson, 2004; Perry, 2012; Strom, 2001; Weisburd & Levin, 1993). Levin (1999), for example, noted that hate crime incidents were twice as likely as other crimes to result in injury to the victim and 4 times more likely than other incidents to require victim hospitalization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, the primary argument for hate crime legislation is that the increased harm associated with hate crime is worthy of increased punishment. A number of studies have supported these arguments regarding physical harm (Fetzer & Pezzella, 2016; Herek, Gillis, & Cogan, 1999; Herek, Gillis, Cogan, & Glunt, 1997; Iganski, 2001; McDevitt, Balboni, Garcia, & Gu, 2001; Perry, 2001). Importantly, however, a number of scholars have also noted that hate crimes are significantly more likely than other crimes to involve the participation of multiple offenders or co-offending (e.g., Dunbar, 1999; Levin, 1999).…”
mentioning
confidence: 99%
“…Despite the differences between data with regard to relative risk, many studies, regardless of data source, find that bias crimes are associated with more injurious outcomes for victims (Fetzer & Pezzella, 2016; Harlow, 2005; B. Levin, 1999; J.…”
Section: Racially Motivated Hate Crimementioning
confidence: 99%